Performance analysis for Secret Message Sharing using different levels of encoding over QSDC - Azahari, Nur Shahirah; Harun, Nur Ziadah; Chuah, Chai Wen; Nawi, Rosmamalmi Mat; Ahmad Zukarnain, Zuriati; Yahya, Nor Iryani (Science and Information Organization, 2024)
It was recently proposed to use quantum secure direct communication (QSDC), a branch of quantum cryptography, to secure data transfers from sender to receiver without relying on computational complexity. Despite the benefits of multiphoton, sending secret messages between several parties in a quantum channel still presents a challenge because the current multiphoton only considers two parties. When more parties are included, the scalability problem becomes apparent. Therefore, the scalable multiphoton approach is needed to allow secure sharing between the legal parties. The manipulation of level encoding provides new opportunities for more efficient quantum information processing and message sharing. This research aims to propose a strategy that uses four-level encoding with the multiphoton approach to share secret messages between multi-party. From the analysis conducted, it has been shown that a high number of level encoding can shorten the time taken for photon transmission between parties and an attacker has a lower probability of chances to launch an attack, however, communication will be affected due to high sensitivity to noise. © (2024), (Science and Information Organization). All Rights Reserved.